2018
DOI: 10.1111/ijcp.13208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 12-week garlic supplementation on symptom relief in overweight or obese women with knee osteoarthritis

Abstract: Although pre- to postintervention knee OA symptoms were improved in overweight or obese women receiving 12 weeks garlic supplement, there was no significant difference in WOMAC changes compared with the placebo group. Further clinical trials are required to investigate the therapeutic value of garlic ingredients, and the potential role of placebo effect, in the management of OA symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Overall, out of 25 dietary supplements identified, 17 of them demonstrated beneficial effect on clinical signs and symptoms. These dietary supplements were krill oil (Suzuki et al, 2016), avocado/soybean unsaponifiables (ASU) (Appelboom et al, 2001), curcumin (Gianni Belcaro et al, 2010;Nakagawa et al, 2014;Panahi et al, 2014;Srivastava et al, 2016), BSE (Sengupta et al, 2008;Sengupta et al, 2010;Vishal et al, 2011), Pycnogenol (Belcaro et al, 2008a;Cisár et al, 2008;Farid et al, 2007), purple fruit passion peel (PFP) extract (Farid et al, 2010), L-carnitine (Malek Mahdavi et al, 2015;Malek Mahdavi, Mahdavi and Kolahi, 2016), Artemisia annua (ART) extract (Hunt et al, 2016), deer bone extract (DBE) (Shin et al, 2018), garlic (Dehghani et al, 2018;Salimzadeh et al, 2018), Momordica charantia (Lim et al, 2018), argan oil (Essouiri et al, 2017) pomegranate juice (PJ) (Ghoochani et al, 2016), sesame seed (Eftekhar Sadat et al, 2013), Phytalgic® (Jacquet et al, 2009), soy protein (Arjmandi et al, 2004) and calcium fructoborate (CFB) (Pietrzkowski et al, 2014). Frestedt et al (2009) reported that Aquamin supplementation is ineffective in symptoms of improvement among OA patients.…”
Section: Dietary Supplements With Positive Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, out of 25 dietary supplements identified, 17 of them demonstrated beneficial effect on clinical signs and symptoms. These dietary supplements were krill oil (Suzuki et al, 2016), avocado/soybean unsaponifiables (ASU) (Appelboom et al, 2001), curcumin (Gianni Belcaro et al, 2010;Nakagawa et al, 2014;Panahi et al, 2014;Srivastava et al, 2016), BSE (Sengupta et al, 2008;Sengupta et al, 2010;Vishal et al, 2011), Pycnogenol (Belcaro et al, 2008a;Cisár et al, 2008;Farid et al, 2007), purple fruit passion peel (PFP) extract (Farid et al, 2010), L-carnitine (Malek Mahdavi et al, 2015;Malek Mahdavi, Mahdavi and Kolahi, 2016), Artemisia annua (ART) extract (Hunt et al, 2016), deer bone extract (DBE) (Shin et al, 2018), garlic (Dehghani et al, 2018;Salimzadeh et al, 2018), Momordica charantia (Lim et al, 2018), argan oil (Essouiri et al, 2017) pomegranate juice (PJ) (Ghoochani et al, 2016), sesame seed (Eftekhar Sadat et al, 2013), Phytalgic® (Jacquet et al, 2009), soy protein (Arjmandi et al, 2004) and calcium fructoborate (CFB) (Pietrzkowski et al, 2014). Frestedt et al (2009) reported that Aquamin supplementation is ineffective in symptoms of improvement among OA patients.…”
Section: Dietary Supplements With Positive Resultsmentioning
confidence: 99%
“…There were more female participants compared to male (69.6%:30.4%). Patients' population in studies done by Dehghani et al (2018), Malek Mahdavi, Mahdavi, and Kolahi (2016), Malek Mahdavi et al (2015 and Salimzadeh et al (2018) included only females. Only one study did not provide information regarding the gender sampled (Eftekhar Sadat et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest plot presenting the standardized mean difference and 95% confidence interval for the impact of nutraceutical supplementation on VAS. 65 which supplements were administered as an adjunctive to symptomatic treatments (NSAIDs and/or analgesics) except nine of them (three 33,47,54 involved patients with knee and/or hip OA, four 24,32,44,52 involved patients with severe knee OA and two 53,55 involved patients for which supplements were administered as a monotherapy and no concomitant treatment were allowed). www.nature.com/scientificreports/ Among studies with medium term of supplementation, WOMAC total score was considerably improved through supplementation with CS in patients with mild to moderate knee OA, Deer bone extract (DBE) in patients with moderate to severe knee OA and PFP and collagen peptides isolated from pork skin (PCP) in patients with mild to severe knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory activity-in in vitro and animal studies, sulfurcontaining compounds from garlic exert anti-inflammatory properties through the inhibition of NF-kappa B activation (a transcription factor that regulates inflammatory response genes) and inducible nitric oxide synthase (iNOS)] and COX-2 expression. Supplementation of daily dose of either 1000 mg garlic tablet for 12 weeks improved significantly stiffness, pain, and physical function in in overweight or obese women with osteoarthritis in a clinical study Butt et al, 2009;Ban et al, 2009;Keophiphath et al, 2009;Kim et al, 2009;Salimzadeh et al, 2018 Cardiovascular health and endothelial function-garlic may slow the development of atherosclerotic process (hardening of the arteries),…”
Section: Referencesmentioning
confidence: 99%